Identification of Mudskipper Species in Mangrove Area of Luwu Timur, Luwu Utara, and Wajo South Sulawesi Indonesia - Darojat, Annisa Zakiyah; Marhendra, Agung Pramana Warih; Kurniawan, Nia (Universitas Brawijaya, 2023)
Mudskipper is amphibious fish that inhabited sandy beaches, mudflat, and mangrove areas. This fish is euryhaline because of its tolerance to varying salinity as well as pH, temperature, conductivity, and dissolved oxygen. This study aimed to identify the taxonomy status of mudskipper in Banua Pangka Mangrove Ecotourism, Seta-Seta Beach, and Masiae River, it was expected to be additional information used as a basis for management and benefaction in taxonomic and ecological aspects. The sampling method of this study was purposive sampling. Morphological identification was carried out by observing morphometric and meristic character. The result found two mudskipper species from three sampling sites, namely Periophthalmus argentilineatus and Periophthalmodon freycineti. Water quality parameter values at three sampling locations were within the optimal range for mudskipper species according to the previous study. The temperatures ranged from 28-33 Celsius, the dissolved oxygen ranged from 2.04-6.74 mg/L, the pH ranged from 6.57-7.1, conductivity ranged from 3.47-41.2 mS/cm, and the salinity ranged from 1.7-2.58 per-mille.